2017
DOI: 10.1371/journal.ppat.1006387
|View full text |Cite
|
Sign up to set email alerts
|

Antigen delivery to dendritic cells shapes human CD4+ and CD8+ T cell memory responses to Staphylococcus aureus

Abstract: Intracellular persistence of Staphylococcus aureus favors bacterial spread and chronic infections. Here, we provide evidence for the existence of human CD4+ and CD8+ T cell memory against staphylococcal antigens. Notably, the latter could provide a missing link in our understanding of immune control of intracellular S. aureus. The analyses showed that pulsing of monocyte-derived dendritic cells (MoDC) with native staphylococcal protein antigens induced release of Th2-associated cytokines and mediators linked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 74 publications
2
19
0
Order By: Relevance
“…Several others also proved that Th17mediated immunity is essential during Sa infection (16)(17)(18)(19). Furthermore, we and others demonstrated that a human memory T cell repertoire exists in healthy individuals (20)(21)(22), underlining the importance of previous exposure.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Several others also proved that Th17mediated immunity is essential during Sa infection (16)(17)(18)(19). Furthermore, we and others demonstrated that a human memory T cell repertoire exists in healthy individuals (20)(21)(22), underlining the importance of previous exposure.…”
Section: Introductionsupporting
confidence: 67%
“…In earlier studies, we saw that SpA induces Treg-associated cytokines in vitro (20). This study aimed to investigate the potential of this B cell superantigen in the induction of human Tregs.…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, IFNγ-producing CD4 + T cells (Th1 cells) were found to contribute to protection against S. aureus skin infections in patients with HIV disease as well as in S. aureus wound and bacteremia infections in mouse models (21)(22)(23). Another study found that the IFNγ produced by human CD8 + T cells contributed to antigeninduced immunity against S. aureus (24). We previously reported that IFNγ and TNF protected against a recurrent S. aureus skin infection in mice deficient in IL-1β (25).…”
Section: Significancementioning
confidence: 99%
“…In fact, healthy donors and patients show a large pool of S. aureus -specific memory T cells that respond to S. aureus with the secretion of IFN-γ and/or IL-17 [ 21 , 22 ]. The existence of CD8+ T cell memory cells and their responses against staphylococcal antigens are important for minimizing inflammation and promoting T cell tolerance [ 20 ]. Moreover, long-term exposure of mice to S. aureus failed to produce IL-2 after an antigen-specific T cell response, suggesting that T cells undergo anergy during persistent infection [ 143 ].…”
Section: Interaction Of Dcs With S Aureus In Tmentioning
confidence: 99%
“…It is well known that most B cells require help by T cells to generate high affinity antibodies, such that the observation of a broad S. aureus -specific antibody repertoire indicates the existence of numerous S. aureus -specific T cells. Several recent studies have provided evidence for robust CD4+ and CD8+ T cell memory of staphylococcal antigens in humans [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%